The effect of grazing history on fungal diversity in broadleaved wood pastures - Mustola, Kaisa (2012)
Traditional rural biotopes such as wood pastures are species rich habitats which have been created by extensive agriculture. In all European countries both the quality and quantity of traditional rural biotopes have drastically decreased during the past century because of increasing farming intensity. This decline is causing a threat to many species, but very little is known about the conservation ecology of fungi living in wood pastures. Considering vascular plants, it is known that sites with long management history have higher species richness compared to abandoned sites. It is also known that species richness is highest with intermediate grazing intensity. In this study I investigated if there is a difference in fungal species richness between presently grazed and presently ungrazed sites. I also investigated the effect of grazing history on fungal species richness and community assembly. In addition, I studied the effect of current grazing intensity on fungal species richness. All my study sites were broadleaved wood pastures in Central Finland. I studied 12 sites of which 6 were presently grazed by domestic animals and 6 were presently not, but had been grazed in the past. Grazing history of the study sites varied between 40-205 years, and considering sites which were presently ungrazed, the time after abandonment varied between 5-40 years. I focused on the agarics, boletoids, ramarioid fungi, Gasteromycetes, Pezizomycetes, and stipitate polypores. I conducted both sample plot surveys and time constrained surveys on each study site and repeated the surveys three times. Overall, I found 313 fungi species in this study. I found out that presently grazed sites do not have more fungal species than presently ungrazed sites. Instead, my results suggest that fungal species richness increases with grazing history duration and sites with long grazing history have a similar community structure even if they are presently ungrazed. I also suggest that with intermediate grazing intensity species richness is the greatest. I conclude that it is very important to know detailed management history when prioritizing management for sites. Moreover, targeting for optimal grazing intensity for sites may be important.